2022
DOI: 10.1002/csr.2366
|View full text |Cite
|
Sign up to set email alerts
|

How do female CEOs affect corporate environmental policies?

Abstract: How do female Chief Executive Officers (CEOs) affect corporate environmental policies? This study develops a theoretical argument by incorporating the role of gender into the context of corporate environmental policies. Specifically, we differentiate corporate environmental policies into sustainable and unsustainable environmental policies. We also hypothesize a positive relationship between female CEOs and corporate sustainable environmental policies because women possess communal qualities and tend to be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…This result supports H1. This is in line with the perspectives of Clarkson et al (2011) and Zhang et al (2023), whereby firms disclose information as they engage in stakeholder management to reduce information asymmetry and obtain incentives when disseminating corporate information to the public.…”
Section: Empirical Analyses and Regression Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This result supports H1. This is in line with the perspectives of Clarkson et al (2011) and Zhang et al (2023), whereby firms disclose information as they engage in stakeholder management to reduce information asymmetry and obtain incentives when disseminating corporate information to the public.…”
Section: Empirical Analyses and Regression Resultssupporting
confidence: 86%
“…Existing research has found that firms' executives play a crucial role in determining whether to engage in socially responsible activities (Davidson et al, 2019), and executive characteristics significantly affect corporate social responsibility disclosure. For instance, compared to firms led by frugal CEOs, those led by materialistic CEOs exhibit lower social responsibility scores, fewer strengths, and more weaknesses (Tsang et al, 2022); female CEOs, compared to male CEOs, generally possess superior public qualities and are more stakeholder-oriented, leading to increased environmental information disclosure (Zhang et al, 2023). Executive compensation structure is a vital component of corporate governance; theoretically, it should have a significant impact on corporate ESG disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that male CEOs are more inclined to disclose information on environmental penalties compared to female CEOs, notwithstanding many studies have found that companies in China with female executives have better CSR performance (Wang, 2016;Xu & Li, 2018;Zhang et al, 2023). Female leaders are typically considered to be more empathetic and socially responsible, and less risky than male leaders (Eagly & Johannesen-Schmidt, 2001).…”
Section: Resultsmentioning
confidence: 61%
“…Following upper echelons theory, this article focuses on an important but understudied CEO characteristic: CEO visibility. Corporate executives have the direct power to influence the fulfillment of corporate environmental and social responsibility (García‐Sánchez et al, 2020; Zhang et al, 2023). CEO visibility is one of the characteristics of a CEO and can be reflected by the CEO's media exposure, that is, the number of times it appears in news media coverage (Blankespoor & De Haan, 2020; Kang & Han Kim, 2017).…”
Section: Research Hypothesesmentioning
confidence: 99%